Species-complex diversification and host-plant associations in Bemisia tabaci: A plant-defence, detoxification perspective revealed by RNA-Seq analyses - Malka, Osnat; Santos-Garcia, Diego; Feldmesser, Ester; Sharon, Elad; Krause-Sakate, Renate [UNESP]; Delatte, Helene; van Brunschot, Sharon; Patel, Mitulkumar; Visendi, Paul; Mugerwa, Habibu; Seal, Susan; Colvin, John; et al. (Wiley-Blackwell, 2018)
Insect-plant associations and their role in diversification are mostly studied in specialists. Here, we aimed to identify macroevolution patterns in the relationships between generalists and their host plants that have the potential to promote diversification. We focused on the Bemisia tabaci species complex containing more than 35 cryptic species. Mechanisms for explaining this impressive diversification have focused so far on allopatric forces that assume a common, broad, host range. We conducted a literature survey which indicated that species in the complex differ in their host range, with only few showing a truly broad one. We then selected six species, representing different phylogenetic groups and documented host ranges. We tested whether differences in the species expression profiles of detoxification genes are shaped more by their phylogenetic relationships or by their ability to successfully utilize multiple hosts, including novel ones. Performance assays divided the six species into two groups of three, one showing higher performance on various hosts than the other (the lower performance group). The same grouping pattern appeared when the species were clustered according to their expression profiles. Only species placed in the lower performance group showed a tendency to lower the expression of multiple genes. Taken together, these findings bring evidence for the existence of a common detoxification machinery, shared between species that can perform well on multiple hosts. We raise the possibility that this machinery might have played a passive role in the diversification of the complex, by allowing successful migration to new/novel environments, leading, in some cases, to fragmentation and speciation.
Keywords: Bemisia tabaci; diet breadth; diversification; host adaptation; insect-plant interactions; species complex